PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBANTUAN APLIKASI ARTICULATE STORYLINE 3 PADA PEMBELAJARAN IPA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS V SEKOLAH DASAR - Amani, Atika Zata; Fitria, Yanti; Zuryanty; Media, Afriza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the lack of innovative technology-based learning media and teachers' limitations in designing interactive media. This study aims to develop interactive multimedia assisted by Articulate Storyline 3 for 5th-grade elementary school science learning using the Problem-Based Learning (PBL) model, integrating images, audio, text, and animation. Using a Research and Development (R&D) approach with the ADDIE model, the study involved 14 trial students SDN 20 Pasaman and 46 research students SDN 05 Pasaman and SD El-Ma’arif, along with their respective classroom teachers. Data were collected via validation questionnaires (material, language, and media experts) and practicality questionnaires. The results show that the multimedia is highly valid, practical, and effective. It achieved an average validity score of 93.33% (86% material, 98% language, 96% media), categorized as "highly valid." Teacher and student practicality reached 88% and 91.71% in the trial school, and 92% and 94.03% in the research schools, all categorized as "highly practical." Effectiveness tests showed positive results with N-Gain scores of 0.76 (trial school), 0.84 (Research School I), and 0.81 (Research School II), indicating a "high" category improvement in learning outcomes. In conclusion, the interactive multimedia assisted by Articulate Storyline 3 using the PBL model for 5th-grade science learning is valid, practical, and effective for the educational process.